Availability, Access and Utilization of E-Resources among Pre-Service Teacher Trainees by Distance - Olaniran, Sunday O.; Duma, M. A. N.; Nzima, D. R.; Kumar, V; Murthy, S; Kinshuk (IEEE 8TH International Conference on Technology for Education, 2016)
The study investigated accessibility to and utilization of electronic resources among pre-service teachers in the National Open University of Nigeria (NOUN). Survey research design was used to carry out the study. Two hundred and thirty eighty (238) undergraduate students studying to obtain Bachelor of Education (B. Ed.) by distance were purposively sampled from Ibadan Study Centre of the institution. The results from the survey revealed that electronic resources in different forms like radio broadcast, e-journals, e-books, and CD-ROM, among others, are available and accessible to the pre-service teacher trainees by distance. However, limited internet connectivity and inadequate access to electricity were shown as major factors constraining most of the participants from accessing and utilizing the available electronic resources. The study recommends for the distance learning providers in developing nations to partner with telecommunication firms and internet service providers with a view to providing constant and affordable internet services to their learners, especially those that are studying to become classroom teachers.
Keywords: -FullBiblioUHMLgen; -RRQ:H:final; -RRQ:U:final; A:Africa; AA:Africa; C:Nigeria; CA:AandC; CL:en; CL:fr; CLL:en; CLS:en; CT:A; CT:C; CT:D; CT:F; CT:P; CT:Q; CT:R; CT:T; D:developing nation; F:access; P:electro; P:service industry; P:teachers; Q:ICT; Q:distance learning; Q:e-learning; R:research design; R:survey; T:trainee; Z:E-Learning; Z:E-Resources; Z:ICT; Z:ODL; Z:Pre-Service Teachers; publicImportV1; ⚠️ Invalid DOI